The yield gap: closing the gap by widening the approach - Snyder, Katherine A.; Miththapala, Sriyanie; Sommer, Rolf; Braslow, Juliet (Cambridge University Press, 2017)
The yield gap has arisen again as a focus for agricultural research to ensure food security and economic growth for farmers around the world. To examine this renewed interest, we carried out a review of key literature in the field of yield gap analysis to identify important gaps in research and analysis. In so doing, both the complexities in yield gap studies emerged along with some significant omissions. Much of the literature and research on the yield gap has been framed by larger concerns and initiatives to raise agricultural productivity. This focus has led to an emphasis on technical solutions such as crop breeding, fertilizer application and other methods to increase production. However, this concentration on the technical usually ignores the wider social, economic and political context that shapes farmer decision making about agricultural production. This context can either discourage or enable farmers to close their yield gap. Additionally, the impact of increased agricultural production through certain technical solutions also often overlooks the wider impact on the landscape and the ecosystem services which underpin agricultural production and livelihoods. We argue that increasing agricultural productivity, and closing the yield gap, must be addressed with this broader approach.